When forecasting and foresight meet data and innovation: toward a taxonomy of anticipatory methods for migration policy - Sara Marcucci; Stefaan Verhulst; María Esther Cervantes (Data & Policy)
The various global refugee and migration events of the last few years underscore the need for advancing anticipatory strategies in migration policy. The struggle to manage large inflows (or outflows) highlights the demand for proactive measures based on a sense of the future. Anticipatory methods, ranging from predictive models to foresight techniques, emerge as valuable tools for policymakers. These methods, now bolstered by advancements in technology and leveraging nontraditional data sources, can offer a pathway to develop more precise, responsive, and forward-thinking policies.